Agency problems in firms with an even number of directors: Evidence from China - He, Wen; Luo, Jin-hui (Journal of Banking & Finance, 2018)
To avoid a tie in voting, most boards have an odd number of directors. We argue that boards with an even number of directors are more likely to be weak monitors because of inefficient decision making and being captured by controlling shareholders. Consistent with this argument, we find that in China boards with an even number of directors have fewer meetings and are more likely to have board members absent from board meetings. Firms with an even number of directors have more tunnelling through intercorporate loans and related party transactions, lower financial reporting quality and higher incidence of accounting irregularities. This evidence is stronger in firms with weaker external monitoring and for directors with weaker incentives to monitor. Finally, we show that firms with an even number of directors are associated with lower market valuation of equity. Our results suggest that corporate boards with an even number of directors in emerging markets are associated with more agency problems.